2019
DOI: 10.1021/acs.est.9b04441
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Spatiotemporal Understanding of Dolomite Dissolution in Sandstone by CO2-Enriched Brine Circulation

Abstract: In this study, we introduce a stochastic method to delineate the mineral effective surface area (ESA) evolution during a recycling reactive flow-through transport experiment on a sandstone under geologic reservoir conditions, with a focus on the dissolution of its dolomite cement, Ca 1.05 Mg 0.75 Fe 0.2 (CO 3 ) 2 . CO 2 -enriched brine was circulated through this sandstone specimen for 137 cycles (∼270 h) to examine the evolution of in situ hydraulic properties and CO 2enriched brine−dolomite geochemical react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…The entire flow‐through experiment consists of three continuous stages: prereaction stage, reaction stage, and postreaction stage, employing the reactive transport system described in Ma et al. (2019) and Lima et al. (2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The entire flow‐through experiment consists of three continuous stages: prereaction stage, reaction stage, and postreaction stage, employing the reactive transport system described in Ma et al. (2019) and Lima et al. (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Effluent fluid samples are collected both at the inlet and the outlet of the reaction cell to infer fluid‐rock reactions during the experiment and to analyze the fluid samples, employing inductively coupled plasma optical emission spectrometry (ICP‐OES) in the Laboratory of Inorganic Chemistry at ETH Zurich (details are provided in Text S2). Using the measured ion concentration, the dolomite reactivity can be calculated as trueR¯.3em=.3emΔC0.3emQfalse/false(xiVfalse), where ΔC is the concentration difference of ion i between the fluid inlet and the fluid outlet, x i is the stoichiometric coefficient of ion i in dolomite, and V is the bulk volume of the sandstone specimen (details are provided in Text S3) (Ma et al., 2019). Furthermore, the theoretical maximum Ca concentration at the experiment conditions is calculated, employing an equilibrium model using PFLOTRAN (Lichtner et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulation around the cell inlet and the cell body assured that the injected fluid temperature is maintained at that of the specimen. A complete description of the flow-through system is provided in Ma et al (2019). A set of preliminary tests showed that our system can reach a maximum temperature of ∼ 140 °C, given the pressure that was applied in this study.…”
Section: Table 1 Specimen Propertiesmentioning
confidence: 99%
“…those occurring at the scale of individual pores in a rock, in fact govern the bulk (i.e. continuum-scale) geochemical interactions between rocks and fluids (e.g., Li et al, 2006;Molins et al, 2012;Plümper et al, 2017;Ma et al, 2019). Indeed, some have argued that the study of pore-scale geochemical processes should be considered a discipline in its own right (Steefel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%